Insight into the mechanism of low friction and wear during the chemical mechanical polishing process of diamond: A reactive molecular dynamics simulation. (August 2020) - Yuan, Song; Guo, Xiaoguang; Huang, Junxin; Gou, Yonjun; Jin, Zhuji; Kang, Renke; Guo, Dongming
Abstract: Chemical mechanical polishing(CMP) is an important method to achieve ultra-precision machining of diamond. However, the friction mechanism during CMP is not well understood due to a lack of information regarding the interface. Here, reactive molecular dynamics simulation was utilized to elucidate the friction behavior under different pressures and flow fates of polishing slurry. Simulation results indicated that pressure could accelerate the passivation of surface, Pauli repulsion between abrasive and substrate could withstand the applied load and prevent the two surfaces from reaching the C–C interaction range. The number of C atoms removed and the subsurface damage of substrate are the function of flow fate and pressure. This provides a theoretical support for the ultra-precision and low-damage machining of diamond. Highlights: The removal rate and subsurface damage are the function of flow and pressure. C–O–C and C–C bonds cause more friction force and friction coefficient. Load can increase the passivation effects of diamond. Removal rate is more sensitive to mechanical force. Low pressure and high flow can achieve the low friction and wear mechanism.